The Effect of Financial Performance on Stock Prices (A Study of Automotive and Component Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020-2024) - Octaviane, Adinda Shabrina; Zulaikah, Zulaikah; Rosilawati, Weny (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2026)
This study aims to analyze the effect of financial performance on stock prices. Financial performance is measured using the Debt-to-Equity Ratio (DER), Total Asset Turnover (TATO), and Current Ratio (CR). This study uses a quantitative approach, secondary data, and 55 samples. Data analysis was performed using multiple linear regression through SPSS. The results show that DER, TATO, and CR simultaneously have a significant effect on stock prices. Partially, all variables have a negative and significant effect on stock prices. Financial performance explains 25.2% of stock price variations, while the remaining variation is influenced by factors outside the research model